Building Social Coherence and Health Literacy: A Salutogenic Perspective on HIV Knowledge and Stigma in Cultural Tourism Communities - Indiastari, Dewi; Candradikusuma, Didi; Rosandy, Milanitalia Gadys; Budiarti, Niniek; Sutanto, Heri; Silvia, Sinta (Universitas Airlangga, 2026)
Background: HIV prevention in rural communities like Ngadas Village (Mount Bromo) faces two major challenges: stigma driven by misconceptions and the need for social resilience amid rapid social and economic transitions influenced by tourism. Limited access to health information and education increases the risk of myths, discrimination, and a poor sense of coherence. This salutogenic study explores how community coherence and cultural strength can serve as resources to reduce HIV stigma and promote resilience. Objective: This study aims to evaluate the level of HIV knowledge and stigma among residents of Ngadas Village and identify factors influencing them. Methods: A cross-sectional quantitative design was used, involving 102 residents who completed a structured questionnaire covering demographics, HIV knowledge, stigma, and attitudes. Data analysis employed chi-square tests and logistic regression (p<0.05) to determine significant predictors. Results: Most respondents (90.2%) were female, with 66.7% having primary education. Although 66.7% demonstrated good general knowledge, a significant gap in health literacy existed—94% misunderstood HIV transmission, wrongly believing it spread through sharing meals or cutlery. This misconception contributed to high stigma levels, with 49% exhibiting poor or high stigma. Higher education (Junior High OR: 10.9; Senior High OR: 7.4) and middle income (OR: 3.4) significantly predicted lower stigma. A more positive attitude was also associated with middle income (OR: 5.4). Conclusion: Misconceptions about casual HIV transmission are the primary source of stigma and barriers to social coherence. Targeted health literacy interventions, combined with economic empowerment and improved access to education, are essential to strengthen community resilience and reduce HIV-related stigma.